Diseño de un plan de marketing para mejorar el posicionamiento de la cooperativa de ahorro y crédito santa rosa de patutan en la ciudad de Latacunga en el periodo 2015 - Lamingo Aimacaña, Byron Patricio (2015)
This research has been developed for the credit union "PATUTAN SANTA ROSA LTDA", located in the canton Latacunga swept Patutan, in order to make a marketing plan to improve the position in the financial market. The credit union "PATUTAN SANTA ROSA LTDA" has not achieved a level of solid and solvent in the financial market of the city of Latacunga positioning, because he had no proper model of effective advertising to publicize their services….